SINGULARITY THEORY and FORCED SYMMETRY BREAKING IN EQUATIONS - Furter, Jacques-Elie; Soares Ruas, Maria Aparecida; Sitta, Angela Maria [UNESP] (Univ Autonoma Barcelona, 2010)
A theory of bifurcation equivalence for forced symmetry breaking bifurcation problems is developed. We classify (O(2), 1) problems of corank 2 of low codimension and discuss examples of bifurcation problems leading to such symmetry breaking.
Keywords: Singularity theory; bifurcation; forced symmetry breaking